REVIEW ON MECHANICAL PROPERTIES OF NON-ASBESTOS COMPOSITE MATERIAL USED IN BRAKE PAD MANUFACTURED BY DIFFERENT METHODS - Mr. Sandip Sopan Shirsath; Prof. M.S.Mhaske (International Journal of Innovations in Engineering Research and Technology, 2021)
Metallic matrix composites are combinations of two or more different metals inter metallic compounds or second phases in which dispersed phases are embedded within the metallic matrix. They are produced by controlling the morphologies of the constituents to achieve optimum combination of properties. Properties of the composites depend on the properties of the constituent phases, their relative amount, and dispersed phase geometry including particle size, shape and orientation in the matrix. In this paper, The mechanical properties, behaviour and micro structural evolution of aluminium metal matrix metalliccomposites fabricated under various process conditions were investigated to understand their process-structure–property relations by optimization process. Addition of silicon carbide to aluminum has shown an increase in its mechanical properties.